Cradling Cultures: A Comparative Study of Ethno-Parenting in Javanese and Korean Lullabies - Octavianisa, Icha Nur; Yulianeta, Yulianeta; Durachman, Memen (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. Lullabies play an important role in transmitting cultural values and intergenerational affection. Its essence and practice are realized through ethnoparenting. However, this research is still relatively understudied, especially because it uses comparative analysis. Thru a comparison of the songs "Tak Léla Léla Lédhung" (Javanese) and "Jajang-jajang Uri Aga" (Korean), this study highlights how the values of love, discipline, and spirituality in traditional oral heritage play a role in shaping modern cross-cultural parenting. The main objective is to explore the implications of both lullabies within the context of the ethnoparenting parenting style. The analysis was conducted using a descriptive qualitative method with Peirce's triadic semiotic approach. This approach allowed the researcher to cohesively integrate linguistic, cultural, and psychological perspectives. The analysis results show how both lullabies contain moral values, strengthen emotional bonds, and serve as a medium for cultural transmission. Overall, this research not only contributes to the preservation of oral traditions but also offers a conceptual framework for applying ethnoparenting in the context of modern cross-cultural parenting. This study opens up opportunities for parents to adapt the ethno-parenting values contained in traditional oral heritage into modern parenting practices. Furthermore, this research can be developed to examine the application of ethnoparenting practices in daily life.